Occupational Therapy and Low Back Pain: Epidemiological profile of patients treated at the Teaching and Assistance Unit in Physiotherapy and Occupational Therapy of the University of the State of Pará (Research, Society and Development, 2022)
Low back pain refers to pain in the lumbar spine. He has a high impact on the economically active population, and it is an important cause of suffering and disability. General goal is identify the pedemiologic profile of patients with low back pain ateended at Unidade de Ensino e Assistência de Fisioterapia e Terapia Ocupacional (UEAFTO). It is a descriptive, quantitative, and prospective study carry out with patients with low back pain in treatment with physical and occupational therapy at UEAFTO, between october/2014 and may/2015. 19.8% has age between 51 to 55 years, 40.5% do not completed elementar school and 57.3% were married. 29% started working between 12-15 years and 36.6% were unemployed. In clinical data 35.1% were diagnosed more than 10 years and 81.7% recognized some causative factor for the advent of low back pain. Self-care 66.4% of them reported difficulties. 71.8% had problems running clothing. In household chores, 87% had difficulties. In work activities, 29% reported difficulties. In relation to the guidelines on the Activities of Daily Living and Working Activities, 55% and 74.8% reported never having received information, respectively. The guidelines are extremely important to improve the manifestations of pain and function in patients with low back pain.